Last tango in cyberspace - Kotler, Steven, 1967- (St. Martin's Press, 2019)
Hard to say when the human species fractured exactly. Harder to say when this new talent arrived. But Lion Zorn is the first of his kind<U+2015>an empathy tracker, an emotional soothsayer, with a felt sense for the future of the we. In simpler terms, he can spot cultural shifts and trends before they happen. It<U+2019>s a useful skill for a certain kind of company. Arctic Pharmaceuticals is that kind of company. But when a routine em-tracking job leads to the discovery of a gruesome murder, Lion finds himself neck-deep in a world of eco-assassins, soul hackers and consciousness terrorists. But what the man really needs is a nap. A unique blend of cutting-edge technology and traditional cyberpunk, Last Tango in Cyberspace explores hot topics like psychology, neuroscience, technology, as well as ecological and animal rights issues. The world created in Last Tango is based very closely on our world about five years from now, and all technology in the book either exists in labs or is rumored to exist. With its electrifying sentences, subtle humor, and an intriguing main character, readers are sure to find something that resonates with them in this groundbreaking cyberpunk science fiction thriller.